Can community interventions change resilience? Fostering perceptions of individual and community resilience in rural places. Issue 2 (15th March 2019) - Markantoni, Marianna; Steiner, Artur Adam; Meador, John Elliot
ABSTRACT: Governments move away from their roles as providers and take on roles as facilitators and enablers. Such transformations provide opportunities for individuals to play an active role in improving the resilience of their communities. However, the effects of such transformations may not be experienced by all communities equally. In the light of the emerging enabling state, which entails a more proactive type of community, this article examines whether community projects can enhance the resilience of hard-to-reach rural communities. Analysis from 345 interviews with rural residents from six communities shows that successful completion of community projects can positively change perceptions of resilience, whereas uncompleted projects negatively affect perceptions of resilience. We conclude that for some hard-to-reach communities, in order to build their resilience, continuous funding support needs to be in place. To enhance the resilience of rural communities, the state must also create opportunities for effective community participation.